The Attitude of Small and Medium Enterprise (SME) Managers about Improper Accounting Practices: A Study from Bangladesh - Akter, Ms Morium; Alam, Kazi Monirul (Feni University Journal, 2026)
Small and medium-sized enterprises (SMEs) are crucial drivers of Bangladesh’s economy. This sector has been pivotal in ensuring economic growth, rapid industrialization, poverty eradication, employment generation, and GDP growth. Bangladesh Bank Report (2019) indicated that there are 7.8 million micro, small, and medium enterprises in Bangladesh, accounting for 25% of the GDP. The International Monetary Fund (IMF) country report (2012) highlighted that SMEs in Bangladesh were responsible for 99% of the private sector industrial establishments, and SMEs have created employment opportunities for 70%-80% of the nonagricultural labor force. Proper accounting practices are immensely significant for a successful and sustainable business. The study aims to determine the attitude of small and medium enterprise (SME) managers regarding improper accounting practices. This empirical study used purposive sampling techniques and a semi-structured questionnaire to collect data. A five-point Likert Scale analyzed the data, Cronbach’s Alpha, correlation, factor analysis, and SPSS.22. The findings revealed that respondents have a positive attitude with the reasons of Lack of Training, Lack of Interest, Lack of Accounting Knowledge, Unnecessary, Requiring more staff, Exposing the Financial Position, and Lack of Guidelines for SMEs. Besides, respondents have a neutral attitude toward the reason for the high cost of hiring qualified accountant records, difficulty in understanding, and lack of time. Moreover, respondents have a positive attitude about the effects of poor record management, improper calculation, and Failure to ascertain the financial position and customer and supplier account balances. Failure to forecast the future, get a loan, and have a neutral attitude affect Poor decision-making and low collection of account balances. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (83-102)